2017
DOI: 10.5530/jppcm.2017.2.20
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-sectional Survey on the Knowledge and Attitudes towards Zika Virus and its Prevention among Residents of Selangor, Malaysia

Abstract: Objective: The objectives of this study were to evaluate the knowledge and attitudes towards ZIKV and its prevention among residents of Selangor, Malaysia. Methods: A pre-tested, selfadministered, cross-sectional survey involving 400 participants was conducted from January to February 2016 in Selangor, a most populated state of Malaysia. Participants were selected using a purposive sampling approach. Descriptive and inferential statistical tests were applied to analyze the data. Results: Of 400 surveys include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
35
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 19 publications
7
35
2
Order By: Relevance
“…Heitzinger, 2017 found in his study that early two thirds of the studied sample reported taking act to avoid Zika infection while existing in a Zika-affected region or travelling. The finding of the current study indicates that about 83.1 of participant have a negative attitude pre-test this is Uncomplicated with Arief et al 2017 (Mohammad et al, 2017) who found that (70.9%) of sample has a favourable attitude, too.…”
Section: Resultssupporting
confidence: 63%
“…Heitzinger, 2017 found in his study that early two thirds of the studied sample reported taking act to avoid Zika infection while existing in a Zika-affected region or travelling. The finding of the current study indicates that about 83.1 of participant have a negative attitude pre-test this is Uncomplicated with Arief et al 2017 (Mohammad et al, 2017) who found that (70.9%) of sample has a favourable attitude, too.…”
Section: Resultssupporting
confidence: 63%
“…The finding in the Qatar study however is similar to 64.0% of respondents that knew that Zika virus did not have a vaccine, in another ZVD study conducted in Selangor, Malaysia in 2016[36].Overall mean percentage basic knowledge level of 37.2%, on Zika virus disease, among women visiting children immunization unit in a tertiary hospital, southeast Nigeria is poor. The pattern of this knowledge among the different educational level of respondents revealed that those with tertiary education qualification demonstrated the highest mean percentage score of 54.4%; while the more educationally qualified group of postgraduate respondents recorded a…”
supporting
confidence: 69%
“…A more encouraging finding of 56.8% was made in Malaysia in 2016 [36]. It has been documented that Zika virus Ribonucleic Acid (RNA) can be detected in semen 188 days after the onset of symptoms [40].…”
Section: Discussionmentioning
confidence: 98%
“…A number of recent studies have been published evaluating the awareness regarding ZIKV disease in different populations,[ 7 8 9 10 11 12 ] but there are very few studies on the awareness of ZIKV disease among medical and health sciences university students. [ 13 14 ] The paucity in research data on awareness of ZIKV disease in the UAE has led to this study.…”
Section: Introductionmentioning
confidence: 99%